Consumption values, destination cues and nostalgia on the attitude in the selection of destination for educational tourism: the mediating role of destination image - Rahman, Muhammad Sabbir; Osman Gani, Aahad M; Hassan, Hasliza; Anwar, Md. Aftab; Abdel Fattah, Fadi Abdel Muniem (Emerals Group Publishing LTD, 2016)
Purpose – The purpose of this paper is to investigate the relationship between consumption values (CV), destination cues (DC), nostalgia and attitude in the selection of destination for educational tourism, and the mediating effect of destination image (DI). Design/methodology/approach – The research applied descriptive statistics, confirmatory factor analysis (CFA) and structural equation modelling techniques. The study tested the reliability and validity of the measurement model through CFA, Cronbach’s α and inter-correlation analyses. This research applied the structural equation model to examine the relationship between the research variables using 250 foreign students. Findings – The results of data analysis support the stated hypotheses. All the direct relationships were significant and positive. However, DI found a partial mediating role among the relationships. Theoretical and practical implications are also discussed. Research limitations/implications – From this research the tourism researchers, policymakers and managers of the respective higher learning institution may develop a complete understanding of the antecedents of attitude formation of the edu-tourists which were not even studied before from the perspective of educational tourism. Originality/value – To date, there have been few empirical studies examining the attitude of the edu-tourists in the selection of a destination for educational tourism. Therefore, understanding the purpose of CV, DC and nostalgia in a tourist’s decision-making operation, and their theoretical relationship, will make both scientific and practical contributions